Analisis pengelompokan jumlah tanaman kehutanan yang diusahakan menurut jenis tanaman di Indonesia - Octavanny, Made Ayu Dwi (Jurusan Matematika FMIPA Universitas Jember, 2024)
One of the problems of archipelagic countries is the lack of maximum utilization of natural resources which has resulted in some areas being left behind. Indonesia is one of those who experience the impact of the lack of utilization of natural resources in the forestry sector. The non-optimal use of forests for planting forestry plants has made most Indonesians use their land as artificial forests, namely to plant forestry plants. Cluster analysis in this case seeks to classify provinces in Indonesia based on the type of forestry plants cultivated. The method used is hierarchical and non-hierarchical. The hierarchical method uses single linkage and complete linkage methods while the non-hierarchical method uses the K-mean method. By making comparisons between methods, the results obtained are that the single linkage method with 8 clusters is the best method for grouping provinces in Indonesia according to the types of plants cultivated. Of the 34 provinces in Indonesia, cluster 1 consists of 27 provinces, while clusters 2 to 8 each consist of only 1 province. Keywords: Cluster analysis, single linkage, complete linkage, K-mean, forest plantsMSC2020: 62H30